2018
DOI: 10.1002/stem.2889
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 Licensed Self-Renewal of Active Adult Neural Stem Cells

Abstract: Adult neurogenesis in the brain continuously seeds new neurons throughout life, but how homeostasis of adult neural stem cells (NSCs) is maintained is incompletely understood. Here, we demonstrate that the DNA methylation adapter ubiquitin-like, containing PHD and RING finger domains-1 (UHRF1) is expressed in, and regulates proliferation of, the active but not quiescent pool of adult neural progenitor cells. Mice with a neural stem cell-specific deficiency in UHRF1 exhibit a massive depletion of neurogenesis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…Since many APC/C substrates are linked to proliferative control, we examined the contribution of UHRF1, and its degradation by APC/C, to cell cycle. Consistent with prior reports, UHRF1 depletion increased the fraction of cells in G1-phase ((65); data not shown). To further investigate the role of UHRF1 in cell cycle, we examined mitotic cells following UHRF1 depletion.…”
Section: Resultssupporting
confidence: 93%
“…Since many APC/C substrates are linked to proliferative control, we examined the contribution of UHRF1, and its degradation by APC/C, to cell cycle. Consistent with prior reports, UHRF1 depletion increased the fraction of cells in G1-phase ((65); data not shown). To further investigate the role of UHRF1 in cell cycle, we examined mitotic cells following UHRF1 depletion.…”
Section: Resultssupporting
confidence: 93%
“…UHRF1 is highly expressed in cancer cells, and it is thought that its level is correlated with the ability of cancer cells to proliferate (Ashraf et al, 2017). As accumulating evidences indicated that UHRF1 is also related to the S phase entry in normal cells (Bonapace et al, 2002;Blanchart et al, 2018), UHRF1 has been thought to play a role in cell proliferation. Therefore, up-regulation of UHRF1 mRNA seen in our in vivo results might be related to the level of DNA methylation in dividing cells such as glial and endothelial cells in the brain under ischemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methyltransferase 1 (DNMT1), the enzyme responsible for the maintenance of DNA methylation, recognizes hemimethylated DNA during replication and establishes the methyl group in the newly synthesized DNA (Bonasio et al, 2010). This process is assisted by several accessory proteins, including the multidomain protein UHRF1 (Blanchart et al, 2018). In a proteomic survey during the cell cycle of HeLa cells, AHCY was found as a partner of DNMT1 (Ponnaluri et al, 2018) (Figure 2).…”
Section: Molecular Effects On Dna Rna and Histone Methylationmentioning
confidence: 99%